Evolution, folding, and design of TIM barrels and related proteins. (June 2021) - Romero-Romero, Sergio; Kordes, Sina; Michel, Florian; Höcker, Birte
Highlights: In-depth sequence analysis reveals that the protein fold universe is more evolutionarily connected than previously assumed. Short ancestral fragments are observed to have propagated to many modern proteins and hint at possible evolutionary pathways. Experimental reconstruction of such events by chimeragenesis and directed evolution allows to test evolutionary relationships. Detailed knowledge of folding landscapes helps to understand evolutionary history and improve protein engineering. The ubiquitous and versatile TIM-barrel fold is a model system to explore evolution, folding, and design. Abstract : Proteins are chief actors in life that perform a myriad of exquisite functions. This diversity has been enabled through the evolution and diversification of protein folds. Analysis of sequences and structures strongly suggest that numerous protein pieces have been reused as building blocks and propagated to many modern folds. This information can be traced to understand how the protein world has diversified. In this review, we discuss the latest advances in the analysis of protein evolutionary units, and we use as a model system one of the most abundant and versatile topologies, the TIM-barrel fold, to highlight the existing common principles that interconnect protein evolution, structure, folding, function, and design.